Investigation of the effects of different drugs on the prevention of intrapleural adhesion in a rat model - Sarıçoban, Barış; Kuru, Murat; Fındık, Sıddıka; Kılınç, İbrahim; Altınok, Tamer (Türk göğüs kalp damar cerrahisi dergisi, 2024)
Background: The aim of this study was to investigate the antifibrinolytic and anti-inflammatory effects of hesperidin, tenoxicam and enoxaparin on intrapleural adhesions in an experimental rat model. Methods: A total of 52 healthy adult male Wistar Albino rats from the same colony were randomly divided into six groups as sham (Group 1), surgical control (Group 2), low-dose hesperidin (Group 3), high-dose hesperidin (Group 4), tenoxicam (Group 5), and enoxaparin (Group 6). All subjects underwent left thoracotomy and except for the sham group, an adhesion model was applied and, postoperatively, the drugs were administered intraperitoneally. On Day 11 postoperatively, the rats were sacrificed and their blood levels of interleukin-1β and interleukin-10 were examined and they were evaluated for pleural adhesion area, adhesion severity score, mesothelial cell proliferation score, mononuclear cell infiltration score, and macrophage infiltration score in the collagen layer. Results: The lowest adhesion area and adhesion severity score were found in Group 6. There was a statistically significant difference between Group 2 and Group 6 and between Group 3 and Group 6 in terms of both parameters (p=0.04 and p=0.02). As for adhesion area, a statistically significant difference was found between Group 5 and Group 6 (p=0.04). Statistically significant differences were also found between Group 2 and Group 5 in terms of mesothelial cell proliferation scores and between Group 1 and Group 4 in terms of mononuclear cell infiltration scores (p=0.03 and p=0.02). Conclusion: Enoxaparin, tenoxicam, and high-dose hesperidin act at different points to prevent adhesion in rats.